The interim report on equal pay of the Commission on the Status of Women - some practical considerations - Gogarty, John (Statistical and Social Inquiry Society of Ireland, 1972)
Obviously goes back to the 19th Century when women were entering manufacturing industry and commerce in increasing numbers. Given particular stimulus during 1914-1918 war as very large numbers of women moved into industry and commerce in the U.K. and other European countries. Economic factors certainly indicate more pressure on equal pay in times of full-employment rather than during depression. Certainly, one main-spring has been the protection of men's earnings but also cultural and political considerations involved.
Symposium on "The interim report on equal pay of the Commission on the Status of Women"
Read before the Society, 3 March 1972
Keywords: Equal pay; Female working conditions; Commission on the status of women; Irish labour market; 314.15